Nexus Between Trading Non-Green Products and Environment: Introducing Non-Green Trade Openness Index - Can, Muhlis; Oluc, Ihsan; Sturm, Bodo; Guzel, Ihsan; Gavurova, Beata; Popp, József (Frontiers in Environmental Science, 2022)
Trade is a significant parameter that may impact environment positively or negatively. However, there is no consensus on this issue among the researchers. It seems likely that tradable products will affect the environmental quality level. However, this requires the separation of the international trade basket. Thus, this research asks whether trade in non-green products affects the level of environmental degradation in the 25 European Union (EU) member states? To answer this question, we develop an index of trade openness in non-green products and empirically investigate whether this index influences the ecological footprint. Non-green trade openness index represents the ratio of the total export and import of non-green products in a country's international trade basket to that country's Gross Domestic Product. Advanced panel estimation techniques are employed for a sample of 25 EU countries over the period between 2003 and 2016. The core finding – supporting the Pollution Haven Hypothesis – is that non-green trade openness reduces environmental degradation. We discuss several implications of this result for recent environmental policies, particularly for the EU climate policy.